One page of text: Eye movements during regular and thorough reading, skimming, and spell checking. (Journal of Eye Movement Research, 2018)
Eye movements during regular reading, thorough reading, skimming, and spell checking of single pages of text were measured, to investigate how high-level reading tasks elicited by instructions affect reading behavior. Word frequency and word length effects were found. All results were compared to regular reading. Thorough reading involved longer total reading times and more rereading, and resulted in higher comprehension scores. Skimming involved longer saccades, shorter average fixation durations, more word skipping, shorter total reading times evenly distributed across the page, and resulted in lower comprehension scores. Spell checking involved shorter saccades, longer average fixation durations, less word skipping, longer total reading times evenly distributed across the entire page, and resulted in lower comprehension scores. Replicating local effects shows that paragraphs maintain sufficient experimental rigor, while also enabling reading analyses from a global perspective. Compared to regular reading, thorough reading was more elaborate and less uniform, skimming was faster and more uniform, and spell checking was slower and more uniform.